Application of G’/G expansion method to two concert problems - Ayati, Zeinab; Biazar, Jafar (International Journal of Applied Mathematical Research, 2012)
In this work G'/G expansion method is used to obtain exact solutions of the Jimbo-Miwa (JM) and Tzitzeica-Dodd_Bullough (TDB) equations. It is shown that G'/G expansion method is straightforward and concise, and its applications are promising.